POLITIK PENDIDIKAN ANAK USIA DINI DI INDONESIA Telaah Historis Raudhatul Athfâl (RA) dan Taman Kanak-Kanak (TK) - Muh. Saerozi (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2009)
Abstract: The Politic of Early Child Education In Indonesia: A Historical Analysis of Raudhatul Athfâl and Kindergarten. Child education at early age for native citizen was out of the attention of the Dutch colonial administration because it did not confirm with its political target. Concern for child education at early age has only emerged to the surface since the Indonesian Republic postindependence era which marked by the introduction of Regulation of 1954. However, this law discriminates the Islamic Kindergarten (Raudhatul Athfâl). The introduction of Law No. 20 of 2003 gives more strength of in the position Raudhatul Athfâl in Indonesia. Sociologically, following the issuance of such legal foundation, competition between Raudhatul Athfâl and Kindergarten (TK) occurred. This competition, consequently lead to the betterment of the quality of Raudhatul Athfâl on side, and the phenomenon of transforming it to Kindergarten on the other.Kata Kunci: pendidikan,taman kanak-kanak, raudatul athfal